A retrospective analysis of 38,652 amniotic fluid karyotype - Ren, Jianyu; Guan, Xiaojiao; Lv, Wenzhe; Yan, Yousheng; Si, Yanmei; Yang, Shufa; Yin, Chenghong (Frontiers in Genetics, 2025)
BackgroundChromosomal karyotype analysis remains a classical and frontline method in prenatal diagnosis, capable of detecting balanced chromosomal abnormalities and providing insights distinct from high‐resolution molecular techniques such as CMA and CNV‐Seq. However, large‐scale studies on the distribution of structural abnormalities and mosaicism in amniotic fluid karyotypes are scarce, with most previous research focusing on common aneuploidies.ObjectiveThe study aimed to elucidate the relationship between chromosomal structural abnormalities and specific chromosomes.MethodsWe established a large‐scale amniotic fluid karyotype database by collecting prenatal diagnostic indications and karyotype analysis results from amniotic fluid samples of 38,652 pregnant women who underwent prenatal diagnosis at the Beijing Obstetrics and Gynecology Hospital.ResultsFrom 2010 to 2024, the proportion of high-risk serological screening cases showed a decreasing trend year by year, while the proportions of high-risk non‐invasive prenatal testing, increased nuchal translucency, and ultrasound abnormalities all showed increasing trends. Among all results, the proportions of non‐mosaic abnormalities, mosaicism, polymorphisms, and normal karyotypes were 4.68%, 0.71%, 1.7%, and 92.91%, respectively. Inversion of chromosome 9 and variations in heterochromatin length of the Y chromosome were the most common polymorphisms. Sex chromosome aneuploidies were more prone to mosaicism. Inversions of chromosomes 9 and Y were the most frequent types of inversions. Robertsonian translocations occurred most commonly between chromosomes 13 and 14, while reciprocal translocations were most frequently observed between chromosomes 11 and 22. Chromosome breakage was most common in chromosomes Y and 1, whereas deletions were most frequently detected in chromosomes X and 5. Isochromosomes mainly appeared in a mosaic form in chromosome X. Among all indication groups, high-risk NIPT was associated with the highest positive rate for unbalanced abnormalities. A searchable karyotype database was setup, which allows users to query abnormal karyotypes identified in this study.ConclusionSpecific chromosomal abnormalities and mosaicisms tend to occur in particular chromosomes. Therefore, attention should be paid to specific chromosomes during karyotype analysis.